Diagnosis and treatment of peripheral exudative haemorrhagic chorioretinopathy. Issue 6 (23rd October 2019) - Vandefonteyne, Sarah; Caujolle, Jean-Pierre; Rosier, Laurence; Conrath, John; Quentel, Gabriel; Tadayoni, Ramin; Maschi, Celia; Le Mer, Yannick; Dot, Corinne; Aknin, Isabelle; Thariat, Juliette; Baillif, Stephanie
Abstract : Purpose: Peripheral exudative haemorrhagic chorioretinopathy (PEHCR) is a rare disorder that is often misdiagnosed. The aim of this study was to better characterise PEHCR and to assess treatment options. Material and methods: Retrospective multicentric chart review. Results: Of 84 eyes (69 patients) with PEHCR referred between 2005 and 2017, the most common referral diagnosis was choroidal melanoma (41.3%). Bilateral involvement was found in 21.7% of cases. Haemorrhagic retinal pigment epithelium detachment was the most common peripheral lesion (53.6%). Maculopathy was associated with peripheral lesions in 65.8% of cases. PEHCR lesions were mostly heterogeneous (58.8%) on B-scan ultrasonography. Choroidal neovascularisation was found in 10 eyes (26.3%) out of 38 eyes that underwent fluorescein angiography. Polyps were observed in 14 eyes (58.3%) out of 24 eyes that underwent indocyanine green angiography. Fifty-one eyes were treated (62.2%). Intravitreal injections (IVTI) of antivascular endothelial growth factor (VEGF) were the most used treatment (36.6%) before laser photocoagulation, photodynamic therapy, vitrectomy and cryotherapy. Only vitrectomy improved visual acuity. Most lesions (65.6%) regressed at the last follow-up visit. Conclusion: In case of PEHCR, multimodal imaging is useful to avoid misdiagnosis, to characterise PEHCR lesions and to guide treatment strategies. Regression of PEHCR lesions was observed in two-thirds of the patients. Vitrectomy improved visual acuity. More than a third of patients underwent anti-VEGF IVTI. Further studies are needed to assess IVTI's efficacy.